2015
DOI: 10.1002/ajmg.a.36953
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis and risk factors related to thyroid dysfunction

Abstract: Thyroid disease is a common problem among women of reproductive age but often goes undiagnosed. Maternal thyroid disease has been associated with increased risk of craniosynostosis. We hypothesized that known risk factors for thyroid disease would be associated with risk of craniosynostosis among women not diagnosed with thyroid disease. Analyses included mothers of 1,067 cases and 8,494 population-based controls who were interviewed for the National Birth Defects Prevention Study. We used multivariable logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
(63 reference statements)
0
21
0
1
Order By: Relevance
“…Large-scale surveillance studies, case studies, as well as cohort studies have identified thyroid hormones as an important influencing factor in calvarial growth and development; as well as, incidence of craniosynostosis [5, 918]. During normal calvarial development, the sutures are formed between the calvarial bones.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale surveillance studies, case studies, as well as cohort studies have identified thyroid hormones as an important influencing factor in calvarial growth and development; as well as, incidence of craniosynostosis [5, 918]. During normal calvarial development, the sutures are formed between the calvarial bones.…”
Section: Introductionmentioning
confidence: 99%
“…Other teratogens affecting the mouth have been defined in animal studies, for example, dioxins and dithiocarbamates . Maternal health challenges have also been associated with mouth anomalies, including diabetes and hyperthyroidism . Overall, the landscape of human mouth developmental anomalies is multifactorial, evolving and incomplete.…”
Section: Steps To Form a Mouth: Xenopus As A Paradigmmentioning
confidence: 99%
“…87 Maternal health challenges have also been associated with mouth anomalies, including diabetes 88 and hyperthyroidism. 89 Overall, the landscape of human mouth developmental anomalies is multifactorial, evolving and incomplete.…”
Section: Human Craniofacial Anomalies Involving the Mouthmentioning
confidence: 99%
“…Hypo-and hyperthyroidism, as well as the presence of thyroid antibodies in the absence of thyroid disease, are associated with increased risk of adverse pregnancy outcomes such as spontaneous abortion and preterm delivery [26][27][28]. Risk factors for thyroid disease include maternal age >30, family history of autoimmune thyroid disease, infertility, diabetes, morbid obesity, and iodine deficiency, some of which have been suggested to be associated with risk of CS [29].…”
Section: Maternal-fetal Thyroid Function and Hypothesesmentioning
confidence: 99%